PEMANFAATAN VIDEO PEMBELAJARAN DALAM PEMBELAJARAN KIMIA UNTUK MENINGKATKAN PEMAHAMAN KONSEP KIMIA - Hartati, Sri; Siregar, Santri Ailannur (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
AbstractThe study aims to determine the effect of using learning videos in improving understanding of chemical concepts. The method used is literature review. The results showed that there are several learning video media that are effective for building understanding of chemical concepts, namely Zenius.Net, Flipped Classroom, environment, VOLTA, and Kinemaster. These media have met the feasibility and validation tests to be used in chemistry learning. Based on the review of various studies, it can be concluded that the use of various types of learning video media can foster concept understanding in chemistry material.Keywords: Learning Video, Concept Understanding, Chemistry Learning